Lacticaseibacillus rhamnosus modulates the inflammatory response and the subsequent lung damage in a murine model of acute lung inflammation (Clinics, 2022)
Objective: The present study investigated the anti-inflammatory effect of the probiotic Lacticaseibacillus rhamnosus (Lr) on lung inflammation induced by Lipopolysaccharide (LPS) of Escherichia coli in C57BL/6 mice.Methods: C57BL/6 mice were divided into four groups: control, LPS, Lr (1 day) + LPS, and Lr (14 days) + LPS. Total and differential cells from Bronchoalveolar Lavage Fluid (BALF) were counted in a Neubauer 40X chamber, and pro-and anti-inflammatory cytokines (IL-1β, IL-6, CXCL-1, TNF-α, TGF-β, and IL-10) were measured by ELISA assay. The analysis of whole leukocytes in blood was performed using the automated system Sysmex 800i. Morphometry of pulmonary tissue evaluated alveolar hemorrhage, alveolar collapse, and inflammatory cells. Pulmonary vascular permeability was assessed by Evans blue dye extravasation, and bronchoconstriction was evaluated in a tissue bath station. The transcription factor NF-kB was evaluated by ELISA, and its gene expression and TLR-2, TLR-4, MMP-9, MMP-12, and TIMP by PCR.Results: The probiotic Lr had a protective effect against the inflammatory responses induced by LPS. Lr significantly reduced pro-inflammatory cells in the airways, lung parenchyma, and blood leukocytes. Furthermore, Lr reduced the production of pro-inflammatory cytokines and chemokines in BALF and the expression of TLRs, MMPs, and NF-kB in lung tissue and maintained the expression of TIMP in treated animals promoting a protective effect on lung tissue.Conclusions: The results of the study indicate that pre-treatment with the probiotic Lr may be a promising way to mitigate lung inflammation in endotoxemia.